Idiopathic Hypertrophic Pachymeningitis: A Case Report from Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2018)
A 52 years old lady presented with sudden severe headache with the history of similar intense headache twenty years back which ended up with left sided blindness. Her physical examination was unremarkable except optic atrophy of the left eye. Investigation included biochemical work up, imaging studies and CSF study. The MRI of brain with contrast gave the key diagnostic clue with characteristic findings of hypertrophic pachymeningitis. Other investigations helped to rule out possible etiologies and the diagnosis idiopathic hypertrophic pachymeningitis was finally made. The patient has been treated with steroid and enjoyed improvement in her yearlong symptoms.Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 110-112